(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Buddha was not primarily an ethical teacher and reformer, not a metaphysician. He disliked metaphysical discussions devold of practical utility. Instead of discussing etophysical questions, which are ethically useless and intellectually useless and intellectually uncertain, the Buddha always tried to enlighten persons on the ost important questions of sorrow, it is origin, its cessation and the path leading to its cessation. The answers to these four questions contitue the essence of the Buddha’s enlightenment. These have come to be known as the four noble truths